SOFT DIPLOMACY KONSULAT JENDERAL REPUBLIK INDONESIA (KJRI) KOTA KINABALU PADA HUBUNGAN PERDAGANGAN INDONESIA – NEGERI SABAH, MALAYSIA - Herning Suryo, Anindya Anggun Mahadianti, Christy Damayanti & (Transformasi, 2016)
Consulate General of Republic of Indonesia Kota Kinabalu as a representative of Indonesiaitself in Sabah, Malaysia has a important part in developing cooperation especially at bilateraltrade using soft diplomacy. The reason of using the soft diplomacy is because it gives aneffective result to fulfilled national interest of a country. The purpose of this research is to findout the implementation of Soft Diplomacy in trade relation Indonesia – Sabah, Malaysia. Theproblem of this research is how Soft Diplomacy from Consulate General of Republic ofIndonesia in trade relation between Indonesia – Sabah, Malaysia. The research result concludethat soft diplomacy that used by Consulate General of Republic of Indonesia Kota Kinabaluthrough 3 aspects cultural, foreign policy and social value implemented to fulfilled Indonesianational interest in bilateral cooperation especially in international trade between Sabah andIndonesia is going well but that doesn‟t show the direct result to make its because to makedecision of cooperation between these two sides provide a long term process. Researchersuggestion are Consulate General of Republic of Indonesia be more maximalize each aspect ofsoft diplomacy and adding more various product at promotion to follow Sabah market taste.Key words : Soft Diplomacy, International Trade, Trade Cooperation Indonesia and Sabah